DEGREE AND FACTORS OF BURNOUT AMONG EMERGENCY HEALTHCARE WORKERS IN INDIA - Baruah, Atanu (Int J Sci Res (Ahmedabad), 2019)
OBJECTIVE: 'Burnout' among emergency healthcare workers needs focus as they make crucial life changing decisions every day and thus, their state of physical and mental wellbeing is an absolute necessity. We aimed to find the level and factors contributing to burnout among the healthcare workers in the busiest Emergency Department of Northeast India. This is the first study done in this department to assess burnout. METHOD: This cross-sectional, questionnaire-based study assessed burnout of the doctors, nurses, and paramedics working in an emergency department of a busy tertiary care teaching institute. Association of demographic variables and factors influencing burnout was explored. Results were analyzed by descriptive and inferential statistics. RESULTS: Low level in emotional exhaustion, moderate level in depersonalization, and moderate level in the lack of personal accomplishment was reported by participants. Children and partner were found to be protective factors. Working hours, duration and status (permanent/contractual) of service influenced burnout. CONCLUSION: Knowing the level of burnout and their determinants can help in formulating measures of improving the work environment. A healthy workforce ensures high quality of healthcare and patient satisfaction.